Thrust into heaven - Schaflechner, Jürgen (Dastavezi, 2020)
Navigating around stereotypes of Islam and non-Muslim belonging in Pakistan, Thrust into Heaven showcases instances of so-called “forced conversion” of Hindu girls to Islam. These incidents often follow a sequence: a young Hindu woman disappears from her house or place of work, and resurfaces again as a married and newly converted Muslim. Once a conversion occurs and has been publicly announced, a combination of legal issues and the street power of extremist religious groups makes it nearly impossible for newly converted women to go back to their former life. On the one hand, some of these conversions are utilized to conceal criminal acts including kidnapping, human trafficking, and rape. On the other hand, they are examples of female agency and ways in which young women navigate through Pakistan’s rigid patriarchal society. Struggling for a dialogic approach to this sensitive topic, this film aims to give room to the various interpretations that emerge around the alleged forced conversion of Hindu women to Islam in Pakistan.
Video, ca. 67 Min., farbig, mit Begleittext des Filmemachers "Thrust into heaven - ambiguity and degradation in multi-mediated ethnographic research", PDF, Seiten 24-35
Dokumentarfilm. - Kurzfilm. Deutschland. 2020
Keywords: Film